Chapter 1 Introduction: A Global Perspective on the Role of Parliamentary Administrations - Christiansen, Thomas; GRIGLIO, Elena; Lupo, Nicola (Taylor & Francis, 2023)
The idea of "parliamentary administration" might appear, at ﬁrst sight, like an oxymoron: parliaments are the domain of politicians, the elected representatives of the people, whereas administrations are commonly understood as the executive bureaucracies carrying out the tasks of governments. The historical development of parliamentary administrations has taken diﬀerent forms in diﬀerent countries, making it diﬃcult to generalize. The most delicate issue regarding parliamentary administrations concerns the nature of the activity they perform. The comparative analysis of the data contained in the various country-speciﬁc chapters demonstrates several commonalities and diﬀerences in relation to certain fundamental organizational and functional options of parliamentary administrations. The very ﬁrst observation in this context concerns the size of parliamentary administrations. A second dimension of framing the distinctive features of parliamentary administrations is the degree of budgetary autonomy. Looking more closely at recent developments, a number of contemporary challenges can be identiﬁed that parliamentary administrations have had to confront in the 21st century.